An alternative routing mechanisms for mobile ad-hoc networks - Ali, Awos Khazal (2008)
Routing is the essential task of transferring packets form source node to destination, or can be described as the process of path finding. A lot of routing mechanisms have been proposed for wired and wireless networks and some of them have been widely used. In Mobile Ad Hoc Network (MANET), every node in the network acts as a router, forwarding packet from one node to another. Since Ad Hoc networks are wireless and the nodes often battery driven, it is very important that the routing protocol in use can handle a large degree of node mobility and at the same time be very energy efficient. The goal of this study is to propose a hybrid routing protocol for MANET based upon existing protocols. NS2 was used to perform the simulation and evaluate the performance of proposed protocol and compare it with existing protocols.